UO‘K 687.157:629 EVALUATION OF HEAT CONDUCTIVITY OF SPECIAL CLOTHING - Alimov, Orif (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
. The importance of special clothing for workers who are working in closed buildings in the exchange of air (heat) between the human body and the environment has been studied. In this case, as samples of special clothes, the actual special clothes which are made of cotton + polyester fiber fabric of automobile factory workers, the special clothes which are made of 100% cotton fiber fabric taken for comparison, and the special clothes made of cotton + modal fiber fabric is recommended as fabric with high hygienic properties were researched.